Quality of life and other patient-reported outcomes following exenteration for pelvic malignancy. Issue 3 (13th January 2014) - Young, J M; Badgery-Parker, T; Masya, L M; King, M; Koh, C; Lynch, A C; Heriot, A G; Solomon, M J
Abstract: Background: Pelvic exenteration is highly radical surgery offering the only potential cure for locally advanced pelvic cancer. This study compared quality of life and other relevant patient-reported outcomes over 12 months for patients who did and those who did not undergo pelvic exenteration. Methods: Consecutive patients referred for consideration of pelvic exenteration completed clinical and patient-reported outcome assessments at baseline, hospital discharge (exenteration patients only), and 1, 3, 6, 9 and 12 months. Outcomes included cancer-specific quality of life (Functional Assessment of Cancer Therapy – Colorectal; FACT-C), physical and mental health status (Short Form 36 version 2), psychological distress (Distress Thermometer), and pain (study-specific composite) scores. Linear mixed modelling compared trajectories between exenteration and no-exenteration groups. Results: Among 182 patients, 148 (81.3 per cent) proceeded to exenteration. There were no baseline differences between the two groups. Among patients who had exenteration, the mean FACT-C score at baseline of 93.0 had reduced by 14·4 points at hospital discharge, but increased to 86·7 at 1 month after surgery and continued to improve, returning to baseline by 9 months. For patients in the no-exenteration group, FACT-C scores decreased between baseline and 1 month, increased slowly to 6 months and then began to decline at 9 months. There were few statistically or clinically significant differences in any patient-reported outcomes between the groups. Conclusion: Quality of life and related patient-reported outcomes improve rapidly after pelvic exenteration surgery. For 9 months after surgery, these outcomes are comparable with those of similar do patients who do not have surgery; thereafter, there is a decline in patients who do not have exenteration. Pelvic exenteration can be performed with acceptable quality of life and patient-reported outcomes. Abstract : Quality of life after pelvic exenteration acceptable